E-CRM A LEVERAGE TOOL FOR CONSUMERS' RETENTION AN ANALYSIS OF IRAQI CONSUMERS' PERSPECTIVE - Mazen Massoud; Nabeel Tallal Abdullah Al-Dulaimi (Scholar Express Journals, 2023)
Information and Communication Technology introduced changes in marketing strategies. E-CRM is derivates from the relational marketing approach. It is a critical resolution to retain consumers. E-CRM adopts a consumer-oriented tactic. It anticipates churn rate complications. However, the execution of ECRM strategies by Iraqi e-commerce is not standardized. A gap results between expectations and practical consequences. This gap is epitomized on a practical and theoretical level. The research aims to highlight the influence of E-CRM on the retention of Iraqi consumers. The quantitative method is used with a hypothetico-deductive approach. It requires the use of an online administered questionnaire. Two steps in collecting and analyzing data are presented. SPSS analyzed the EFA. Findings have proven that E-CRM has a direct positive impact on retention. Five items were retained for consumer loyalty. E-CRM dimensions improve consumer retention. Consumer retention is crucial for e-commerce. Websites should personalize online services and solve online complaints directly.
Keywords: E-CRM; E-Commerce; Retention; Churn Rate